The SOD1 Inhibitor, LCS-1, Oxidizes H2S to Reactive Sulfur Species, Directly and Indirectly, through Conversion of SOD1 to an Oxidase - Kenneth R. Olson; Tsuyoshi Takata; Kasey J. Clear; Yan Gao; Zhilin Ma; Ella Pfaff; Karthik Mouli; Thomas A. Kent; Prentiss Jones; Jon Fukuto; Gang Wu; Karl D. Straub (MDPI AG, 2024)
LCS-1, a putative selective inhibitor of SOD1, is a substituted pyridazinone with rudimentary similarity to quinones and naphthoquinones. As quinones catalytically oxidize H2S to biologically active reactive sulfur species (RSS), we hypothesized LCS-1 might have similar attributes. Here, we examine LCS-1 reactions with H2S and SOD1 using thiol-specific fluorophores, liquid chromatography-mass spectrometry, electron paramagnetic resonance (EPR), UV-vis spectrometry, and oxygen consumption. We show that LCS-1 catalytically oxidizes H2S in buffer solutions to form RSS, namely per- and polyhydrosulfides (H2Sn, n = 2-6). These reactions consume oxygen and produce hydrogen peroxide, but they do not have an EPR signature, nor do they affect the UV-vis spectrum. Surprisingly, LCS-1 synergizes with SOD1, but not SOD2, to oxidize H2S to H2S3-6. LCS-1 forms monothiol adducts with H2S, glutathione (GSH), and cysteine (Cys), but not with oxidized glutathione or cystine; both thiol adducts inhibit LCS-1-SOD1 synergism. We propose that LCS-1 forms an adduct with SOD1 that disrupts the intramolecular Cys57-Cys146 disulfide bond and transforms SOD1 from a dismutase to an oxidase. This would increase cellular ROS and polysulfides, the latter potentially affecting cellular signaling and/or cytoprotection.